Technologies for value addition in food products and processes - Deka, Sankar Chandra 1965-; Hulle, Nishant Rachayya Swami 1985-; Seth, Dibyakanta 1980- (Apple Academic Press, 2020)
The new volume looks at some important emerging food processing technologies in light of the demand for functional food products and high-value and nutritionally rich products. Technologies for Value Addition in Food Products and Processes covers a selection of important recent developments in food processing that work to enrich or maintain nutritional value of food products, including such applications as non-thermal plasma, refractance window drying, extrusion, enzyme immobilization, and dry fractionation. Dry fractionation, in particular, has emerged as a sustainable alternative to wet processes in the last three decades for producing protein concentrates from legumes. The chapters on fish processing cover both traditional knowledge and advances in fish processing technologies. A chapter on bioethanol production discusses the past and present status of the industry, focusing on economic feasibility and environmental viability. The chapter on traditional foods discusses fermentation process and nutritional aspects of ethnic foods followed by the Rabha-Hasong, Mishing and Karbi communities of Assam, India. With the contribution from experts in their respective fields, this book provides new information on novel food processing technologies"--